Analysis of pan-African Centres of excellence in health innovation highlights opportunities and challenges for local innovation and financing in the continent - Nwaka Solomon; Ochem Alexander; Besson Dominique; Ramirez Bernadette; Fakorede Foluke; Botros Sanaa; Inyang Uford; Mgone Charles; Adae-Mensah Ivan; Konde Victor; Nyasse Barthelemy; Okole Blessed; et al. (BMC, 2012)
Abstract A pool of 38 pan-African Centres of Excellence (CoEs) in health innovation has been selected and recognized by the African Network for Drugs and Diagnostics Innovation (ANDI), through a competitive criteria based process. The process identified a number of opportunities and challenges for health R&D and innovation in the continent: i) it provides a direct evidence for the existence of innovation capability that can be leveraged to fill specific gaps in the continent; ii) it revealed a research and financing pattern that is largely fragmented and uncoordinated, and iii) it highlights the most frequent funders of health research in the continent. The CoEs are envisioned as an innovative network of public and private institutions with a critical mass of expertise and resources to support projects and a variety of activities for capacity building and scientific exchange, including hosting fellows, trainees, scientists on sabbaticals and exchange with other African and non-African institutions.